Extrahepatic manifestations of hepatitis E virus. (April 2016) - Kamar, Nassim; Marion, Olivier; Abravanel, Florence; Izopet, Jacques; Dalton, Harry R.
Abstract: Hepatitis E virus can cause acute, fulminant and chronic hepatitis and has been associated with a range of extrahepatic manifestations. Guillain–Barré syndrome, neuralgic amyotrophy and encephalitis are the main neurological manifestations associated with acute and chronic hepatitis E virus infection. Renal injuries have been also reported, including membranoproliferative glomerulonephritis with or without cryoglobulinemia and membranous glomerulonephritis. Acute pancreatitis, haematological disorders and other autoimmune extrahepatic manifestations of hepatitis E virus, such as myocarditis and thyroiditis, have been also reported. In this comprehensive article, we review all published reports describing hepatitis E virus–associated extrahepatic manifestations.